Analisis Pengaruh Kawasan Ekonomi Khisus (KEK) Mandalika Terhadap Pertumbuhan Ekonomi di Kabupaten Lombok Tengah - Marsha Ayu Safitri; Hj Emi Salmah (Ikatan Da'i Indonesia, 2026)
This study aims to analyze the effect of the Mandalika Special Economic Zone (SEZ) on economic growth in Central Lombok Regency by examining the influence of Foreign Direct Investment (FDI), road infrastructure, and Regional Original Revenue (PAD) on Gross Regional Domestic Product (GRDP). This research employs a quantitative method using multiple linear regression analysis with time series data from 2015 to 2024 obtained from the Central Bureau of Statistics (BPS). The results show that partially, road infrastructure has a positive and significant effect on GRDP, while FDI and PAD do not have a significant effect despite showing a positive relationship. Simultaneously, FDI, road infrastructure, and PAD have a significant effect on GRDP, with a coefficient of determination (R²) of 0.842682, indicating that the model has strong explanatory power. These findings suggest that the existence of the Mandalika SEZ has not yet fully provided a direct impact through foreign investment and regional revenue, but is more influenced by the role of infrastructure in driving regional economic activities. Therefore, it is necessary to optimize the linkage between investment, infrastructure, and local economic sectors to ensure that the benefits of the Mandalika SEZ can be more widely and evenly distributed.